A produção de corpos pelo discurso biotecnológico no currículo de formação em ciências biológicas - Paranhos, Mayra Louyse Rocha (2019)
The opening of the genetic code and its once-impossible mapping has come to fruition, and the practices of biology and life-study engineering are increasingly popularized among societies. In this sense, I set out to analyze the production of bodies by the biotechnological discourse in the training curriculum in Biological Sciences (CB). I take into account the discussion of the body that is managed by the power over life and ground this dissertation in a poststructuralist perspective, whose methodological reference is the Foucaultian analysis of discourse. The empirical material was the result of the reports of the licenciandas / os in CB of the Federal University of Sergipe (UFS). The research that bases this work is organized in two moments. In the first one, two focus groups were held with CB students, in which topics of interest for this research were discussed, such as: the production of bodies in the biotechnology era, from the problematization of genetic tests; the training of CB teachers to work in basic education; curriculum, in particular the CB course curriculum. In the second moment, semi-structured interviews were conducted, to provide greater freedom of speech to the interviewees. Given the advances in science and technology (S&T) and the controversies that are generated from these advances, the empirical material of this research allowed me to discuss the training curriculum of the CB teachers, questioning: the possibilities of working the controversies that generate polemics immersed in the control society and its performance in the curriculum; How the body is worked on the curriculum of CB and what the body conception for these / is students; And, as the biotechnologies that operate with the body allow reflections and criticism on the development of S&T. I approach scientific truths and their authoritative sayings on life. Questioned to be teacher of CB and the incumbencies of Science Teaching (CE) based on the triple reason, progress and ethics. Problematizing this supposed neutrality produced by modern science, discussing what would be science and its products. It deals with life, from the perspective that comes from different cultures, considering that each society, religion and / or institution, can establish its own parameters that determine when and how one has a life and how this can be equated in society. Question the right to life and death and the maintenance of monsters, which are those bodies that do not meet the standard of health and beauty propagated by these genetic tests and which would not have been possible if they had undergone a procedure of this size. I bring the scientific truths and their authority to advocate on bodies and life; to whom this type of genetic test is directed; issues involving pre-implantation genetic testing (PGD), such as abortion and neo-Nazism; the media in the visualization of the problematizations that surround the PGD. Through this work, I reverberate about the positioning of a given order that emerges from the 21st century, biotechnology, on the "manufacture" of healthy bodies that meet the required standards, highlighting the need to problematize the sayings produced in the research as scientific truths and who legitimize their place of authority to advocate on bodies and life. I conclude how the subjects involved cling to discourses that vary between the scientific and the religious.